2022
DOI: 10.1039/d2tc00626j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular clustering behaviour in the cybotactic nematic phase of a spin-labelled liquid crystal

Abstract: A newly synthesised liquid crystalline nitroxide radical with a terminal trifluoromethyl group exhibits a cybotactic nematic phase. EPR spectroscopy of the spin-labelled LC implies that molecules move into and out of the cybotactic clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…where I L and I R are the fluorescence intensity of left and right CPL, respectively. Moreover, we found that the CPL of FCLC particles went through the process of first increasing and then decreasing and finally chirality inversion with the increase of chiral dopant addition, the liquid crystal molecular arrangement in FCLC particles went through the process of changing from disordered to bipolar structure to radially aligned structure, and the liquid crystal phase went through the transition from cybotactic phase , to cholesteric phase and finally to twist grain boundary phase. Thus, it is proved that the key to the chirality inversion of CPL in FCLC particles is the formation of the twist grain boundary phase. In addition, we have prepared labels (Figure c) with dual anticounterfeiting functions using FCLC with small particle size (∼1.85 μm) particles based on the structural color and fluorescence color, in which polarized light and fluorescence act as one and 2-fold decryption keys, respectively.…”
Section: Introductionmentioning
confidence: 93%
“…where I L and I R are the fluorescence intensity of left and right CPL, respectively. Moreover, we found that the CPL of FCLC particles went through the process of first increasing and then decreasing and finally chirality inversion with the increase of chiral dopant addition, the liquid crystal molecular arrangement in FCLC particles went through the process of changing from disordered to bipolar structure to radially aligned structure, and the liquid crystal phase went through the transition from cybotactic phase , to cholesteric phase and finally to twist grain boundary phase. Thus, it is proved that the key to the chirality inversion of CPL in FCLC particles is the formation of the twist grain boundary phase. In addition, we have prepared labels (Figure c) with dual anticounterfeiting functions using FCLC with small particle size (∼1.85 μm) particles based on the structural color and fluorescence color, in which polarized light and fluorescence act as one and 2-fold decryption keys, respectively.…”
Section: Introductionmentioning
confidence: 93%